2017
DOI: 10.11114/jets.v5i12.2823
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Qatari Licensure System: Giving Voice to Educators at Government-Funded Schools

Abstract: The issue of developing a comprehensive licensure system aligned with professional standards for teachers and school leaders has received considerable attention in recent years. As part of the Qatari educational reform in recent years, teachers and school leaders are held accountable to offer quality education for all students. The current study thus examined the experiences of educators in Qatar with the licensure process currently implemented at government-funded school. Using a survey study design, a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Professional teachers according to Jeanpierre et al (2005), Liakopoulou (2011), andAbu-Tineh et al (2017) are teachers who have competence in the aspects of the learning process and strategy; teachers who can understand the psychology of students; are able to motivate and pay attention to all students.…”
Section: Resultsmentioning
confidence: 99%
“…Professional teachers according to Jeanpierre et al (2005), Liakopoulou (2011), andAbu-Tineh et al (2017) are teachers who have competence in the aspects of the learning process and strategy; teachers who can understand the psychology of students; are able to motivate and pay attention to all students.…”
Section: Resultsmentioning
confidence: 99%
“…This quantitative study utilized the survey method as its research design. Based on the related literature [69,83,[92][93][94][95]. The present researchers developed the Career Advancement Survey (CAS) utilized in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Abu-Tineh et al ( 2017) examined how educators in Qatar perceive professional standards in education. The investigation found that many teachers thought professional standards must be revised [83]. The standards were unclear and included details that were not needed.…”
Section: Professional Competencies and Professional License For Caree...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the broader reform initiative was discontinued nearly a decade later [27], the teaching licensure protocol remained an integral part of Qatar's teaching professionalism framework. However, there have been significant changes in the teaching licensure model in Qatar, with a temporary freeze period in between [29]. The original portfolio-based licensure model, which was initiated in 2008, was halted in 2015 due to opposition from the Qatari educational community, media coverage, and perceived incompatibility with local educational context and ideology [30].…”
Section: Introductionmentioning
confidence: 99%